A Critical Review of SNEDDS: Mechanistic Basis, Formulation Advances, and Future Directions in Oral Drug Delivery - Prachi Suresh Patil; Prajakta Kirankumar Kavathekar; Gauri Sachin Admuthe; Sonali Dasharath Mali; Rabbika Rajjak Attar; Pravin Kondiba Pawar (Current Advances in Medicine, 2026)
Abstract: Although many newly developed therapeutic compounds exhibit low bioavailability due to poor aqueous solubility and limited gastrointestinal permeability, oral drug delivery remains the preferred route of administration because of its simplicity, convenience, and high patient compliance. An efficient lipid-based method to get around these restrictions is self-nanoemulsifying drug delivery systems. These nanoscale droplets greatly improve mucosal penetration, surface area for dissolution, and solubilization of the medication. Furthermore, SNEDDS enhances the bioavailability of BCS class II and IV drugs by promoting lymphatic absorption, reducing first-pass metabolism, and maintaining drugs in a solubilised state. System efficiency is mostly determined by critical formulation variables, including droplet size, HLB, lipid selection, surfactant content, and thermodynamic stability. Sustained solubilization, modulation of intestinal permeability, reduced efflux activity, and enhanced lymphatic transport collectively contribute to improved drug absorption. Recent developments have expanded SNEDDS into specialized categories, including ligand-modified targeted SNEDDS for site-specific action, controlled-release SNEDDS for sustained delivery, solid SNEDDS for improved stability and handling, and supersaturated SNEDDS to prevent drug precipitation. These developments have made SNEDDS more adaptable, effective, and patient-friendly. Further studies are anticipated to maximise their therapeutic potential.